Allergic contact dermatitis in pediatric patients with type 1 diabetes: An emerging issue. (April 2020) - Lombardo, Fortunato; Salzano, Giuseppina; Crisafulli, Giuseppe; Panasiti, Ilenia; Alibrandi, Angela; Messina, Maria Francesca; Pajno, Giovanni Battista; Caminiti, Lucia; Passanisi, Stefano
Highlights: Skin reaction could hamper the spread of new diabetes technological devices. Allergic contact dermatitis is the most insidious of dermatological complications. Allergic contact dermatitis is quite frequent among children with type 1 diabetes. Allergic contact dermatitis seems not to be associated with atopic predisposition. Devices manufacturers should provide detailed information about adhesives. Abstract: Aims: Aim of our observational study was to assess the prevalence of allergic contact dermatitis among children and adolescents with type 1 diabetes who use technological devices for diabetes treatment and its management. Secondary outcome was to identify possible clinical and/or demographic variables that could be associated to contact dermatitis. Methods: Among a total of 215 patients using insulin pumps and/or glucose sensors followed-up at our Pediatric Diabetes Centre between January and September 2018, 64 patients were enrolled and 42 (19 male and 23 female) completed the study. Demographic and clinical features of the study population were statistically analysed. All the patients underwent patch testing with specific allergens belonged to resin and acrylate classes. Results: Eighteen patients experienced skin reactions suggestive of allergic contact dermatitis, demonstrating a prevalence of 8.4%. None of the demographic or clinical variables were associated to skin reactions. Colophonium was the most identified sensitizing allergen (87.5% of the cases). Conclusions: The rate of sensitization to allergens included into diabetes devices among pediatric patients is higher than commonly assumed. Well-designed studies are needed to better investigate the association between type 1 diabetes and allergic contact dermatitis. Moreover, we suggest that manufactures should supply detailed information about adhesives in order to avoid dermatological complications and consequently a worsening of disease management and patients' quality of life.